2020
DOI: 10.1073/pnas.2005722117
|View full text |Cite
|
Sign up to set email alerts
|

A Zika virus envelope mutation preceding the 2015 epidemic enhances virulence and fitness for transmission

Abstract: Arboviruses maintain high mutation rates due to lack of proofreading ability of their viral polymerases, in some cases facilitating adaptive evolution and emergence. Here we show that, just before its 2013 spread to the Americas, Zika virus (ZIKV) underwent an envelope protein V473M substitution (E-V473M) that increased neurovirulence, maternal-to-fetal transmission, and viremia to facilitate urban transmission. A preepidemic Asian ZIKV strain (FSS13025 isolated in Cambodia in 2010) engineered with the V473M s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 36 publications
0
68
0
1
Order By: Relevance
“…The envelope (E) protein is the main component of the icosahedral capsule envelope of the ZIKV particles, responsible for the virus attaching to and entry the host cell, as well as for host adaption, immune recognition and virus pathogenesis. It is also the major protein for inducing neutralizing antibodies against virus infection (Dai et al, 2016;Fontes-Garfias et al, 2017;Giraldo et al, 2020;Sapparapu et al, 2016;Shan et al, 2020;Stettler et al, 2016). It has a total length of 505 amino acids, similar to other flavivirus E proteins, and consists of four domains.…”
Section: Envelope Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…The envelope (E) protein is the main component of the icosahedral capsule envelope of the ZIKV particles, responsible for the virus attaching to and entry the host cell, as well as for host adaption, immune recognition and virus pathogenesis. It is also the major protein for inducing neutralizing antibodies against virus infection (Dai et al, 2016;Fontes-Garfias et al, 2017;Giraldo et al, 2020;Sapparapu et al, 2016;Shan et al, 2020;Stettler et al, 2016). It has a total length of 505 amino acids, similar to other flavivirus E proteins, and consists of four domains.…”
Section: Envelope Proteinmentioning
confidence: 99%
“…Another study suggests that the E protein glycosylation may contribute to ZIKV pathogenesis via enhancing infection of lectin-expressing leukocytes (Carbaugh et al, 2019). Recently, Shan et al revealed that ZIKV acquired an evolutionary mutation in the E protein (V473M), before its 2013 transmit to the Americas, which is a critical determinant for enhanced neurovirulence, mother-to-child transmission, and viremia to facilitate urban transmission (Shan et al, 2020). This study explains, in a large part, the reason of ZIKV reemergence and enhanced pathogenicity.…”
Section: Envelope Proteinmentioning
confidence: 99%
“…Shan et al 32 showed that there was a single mutation in the viral envelope gene (E-V473M) of Zika virus which might be the underlying cause for the enhancement in its virulence and the high rate of maternal-to-foetal transmission during pregnancy seen since 2013. Liu et al 33 also showed that the NS1 (A188V) mutation is responsible for an enhancement in the virulence of Zika virus and is the underlying cause for the most recent outbreak in the Americas.…”
Section: Mutations Of Zika Virusmentioning
confidence: 99%
“…Another mutation identified via phylogenetic analysis, E-V473M, increased viremias in non-pregnant cynomolgus macaques and neurovirulence in 1-day old mice inoculated intracranially, but did modify ZIKV RNA levels in Ae. aegypti (19). Since prM-S139N…”
Section: Introductionmentioning
confidence: 99%